Contemporary Art from Portugal: Western Lines. - Molder, Jorge (Tokyo : Foundation Arc-en-Ciel, 1993)
Almeida, Helena ; Chafes, Rui ; Gaëtan ; Proença, Pedro ; Rego, Paula ; Cabrita Reis, Pedro ; Sanches, Rui ; Sarmento, Juliao
Tentoonstelling 'Contemporary Art from Portugal: Western Lines', Hara Museum of Contemporary Art, Tokyo, 11.09.1993 - 19.12.1993.
Engels
Japans
boek
Keywords: Portugal